أثر القياس المحاسبي عن محاسبة الموارد البشرية وأثرها على مصادر البيانات المالية دراسة حالة للقياس المحاسبي للموارد البشرية للشركة الجزائرية لتوزيع الكهرباء والغاز بولاية الوادي - مروة, تواتي ابراهيم; ليلى, درويش; منال, خطاب (University of eloued جامعة الوادي, 2021)
"هدفت هذه الدراسة إلى إبراز أثر القياس المحاسبي على محاسبة الموارد البشرية وأثرها على مصادر البيانات المالية، فإن نجاح المشاريع الاقتصادية في تحقيق أهدافها يعتمد بدرجة كبيرة على كفاءة وفعالية الموارد البشرية العاملة بها من حيث القياس وتكاليف الاختيار والتعيين والتدريب وتطوير الأصول البشرية وتعديل القيمة الاقتصادية لها، فقد سعت الكثير من المؤسسات لتطبيق هذا المفهوم في إطار المحاسبة عن الموارد البشرية بطريقة منظمة حيث ساهم التقدم العلمي في توجيه الفكر المحاسبي إلى إعادة النظر في معالجة الموارد البشرية. وإدراكا من الباحثين لأهمية توفر معلومات عن تلك الموارد فقد نشطت المحاولات لوضع أسس للمحاسبة عن الموارد البشرية وإثبات اعتبار المورد البشري كمورد اقتصادي وبيان أثره غي القوائم المالية ومعرفة أهميته في تحقيق غايات إستراتيجية، إضافة إلى ضرورة اتخاذ الإجراءات والسياسات الرسمية من أجل تطبيق محاسبة الموارد البشرية ونخص بالذكر طريقة التكلفة التاريخية، وسنحاول في هذه الدراسة إبراز أهم تلك الصعوبات التي تواجه تطبيق المحاسبة للموارد البشرية وكيفية معالجتها وتسجيلها وفق النظام المحاسبي بمؤسسة سونلغاز بالوادي لسنة2016-2017. ومن أبرز نتائج دراستنا أن عملية قياس الأفراد وفق لمحاسبة الموارد البشرية تفترض بقاء الأفراد بالمؤسسة ووضع مسار محدد للتطور الوظيفي للأفراد وتطبيق ذلك في الواقع العلمي يعتبر أمرا صعبا، وأن النموذج القائم على التكلفة التاريخية يعد في الوقت الراهن النموذج الأنسب مع الأنظمة المحاسبية الحالية وطرق عرض القوائم المالية، ولكن لحد الآن لم يتم الاتفاق على نموذج محدد يتم اعتماده لقياس الموارد البشرية نظراً لكثرة المتغيرات المتعلقة بهذا العنصر، مما جعل البحوث لا تزال مستمرة بهدف إيجاد أسلوب متكامل للقياس المحاسبي لهذا العنصر الهام. "This study aimed to highlight the impact of accounting measurement on human resources accounting and its impact on financial data sources. Many institutions have sought to apply this concept in the framework of accounting for human resources in an organized manner, as scientific progress has contributed to directing accounting thought to reconsider the treatment of human resources. Realizing the importance of providing information on these resources, attempts have been made to lay the foundations for accounting for human resources, to prove that the human resource is considered an economic resource, and to show its impact on the financial statements, and to know its importance in achieving strategic goals. In addition to the need to take official procedures and policies in order to apply human resources accounting, especially the historical cost method. In this study, we will try to highlight the most important difficulties facing the application of human resources accounting and how to address and record them according to the accounting system of the Sonelgaz Foundation in the Valley for the year 2016-2017. One of the most prominent results of our study is that the process of measuring individuals according to human resources accounting assumes that individuals remain in the institution and that a specific path for the career development of individuals and the application of this in scientific reality is considered a difficult matter, and that the model based on historical cost is currently the most appropriate model with the current accounting systems and list display methods Financial, but so far no agreement has been reached on a specific model to be adopted for measuring human resources due to the large number of variables related to this element, which made research still ongoing with the aim of finding an integrated method for accounting measurement for this important element.
مذكرة ماستر محاسبة
Keywords: محاسبة الموارد البشرية، القياس المحاسبي، البيانات المالية.; human resource accounting, accounting measurement, financial data.